Postopek izbire sistema načrtovanja in krmiljenja proizvodnje - Starbek, Marko (Strojniški vestnik, 2000)
The basic task of a production planning and control (PPC) system is to solve the complex tasks of production planning and control in a company. There are several computer-aided PPC systems commercially available, and companies find it difficult to select the optimal system from the wide variety of systems available on the market. This paper presents the general structure of a PPC system, showing the logical execution sequence of production planning and control tasks, and describes a two-phase selection of an optimal PPC system. The two-phase procedure of selecting on optimal PPC system was tested in a company that produces locks and metal parts. Based on the test results the company management selected the optimal PPC system.
Keywords: sistemi PPS; koristnost; funkcije sistemske; strukture sistemov; proizvodnja; načrtovanje; sistem PPS